RE-READING OF VULNERABLE MINDS IN COSTUME- A SELECT STUDY ON TWO MALAYALAM MOVIES - Karmel, Cynthia S.; M, Aiswarya Lakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Masculinity as depicted in visual culture is often appropriated as the ideal to adhere in most of the representations, whether it is cinema or performing arts. Patriarchal order tends to project masculinity as the source of power from which the matrix of a society is outlined. Representation of masculinity on screen and their dimensions convey human experiences in a hitherto unperceived way. Apart from being a muscular figure which is categorized against a vulnerable woman, the dawn of 20th century has witnessed varied representations onscreen including sensitive, vulnerable, possessive protagonists trapped in a well-toned muscular body striving for an identity. Performing arts, unlike movies gives space for representing varying emotions pertaining to their role in society using costumed characters and images.